2014
DOI: 10.1016/j.ejphar.2014.01.027
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of clonidine in the isolated rat testicular capsule

Abstract: The testicular capsule contracts in response to noradrenaline and adrenaline, but the effects of adrenoceptor agonists, as for instance clonidine, had not yet been thoroughly evaluated. The testicular capsule from adult male Wistar rats was isolated and mounted in organ bath and cumulative concentration curves were performed for clonidine and other adrenergic agonists in the absence or presence of α-adrenoceptors antagonists. The order of potency for agonists (pD2) was clonidine=adrenaline>UK 14,304>noradrenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…More specifically, the use of medication for a longer time period brutally affects the male fertility, while the short courses of medication caused temporary infertility. 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, the use of medication for a longer time period brutally affects the male fertility, while the short courses of medication caused temporary infertility. 5 …”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the use of medication for a longer time period brutally affects the male fertility, while the short courses of medication caused temporary infertility. 5 The spermatogenesis is the process of development of spermatozoa through a series of multiple events. In testes, the process of spermatogenesis takes place in the lumen of seminiferous tubules, and almost 90% of testes consist of seminiferous tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pharmacological parameters E max (maximal contraction) 35,40 and pEC 50 (agonist potency ‐ the negative log of EC 50 ) 41 were graphically determined from concentration response curves in order to allow comparisons between agonist curves in the absence or presence of dipyrone or ASA.…”
Section: Methodsmentioning
confidence: 99%
“…There are limited studies evaluating receptor classification in testicular arteries, particularly in the canine model. However, one study indicated that α 2 -adrenoceptors likely contribute to smooth muscle contraction in the rat testicular capsule [23]. As it has been shown that canine vessels in different body regions have varied α-adrenoceptor subtypes [24], it is likely that α 2adrenoceptors may be more prominent in canine testicular arteries.…”
Section: Plos Onementioning
confidence: 99%